Prevalence of tobacco use among rural women of Mohanpur block, West Tripura district - Rituparna Das; Subrata Baidya (Al Ameen Medical College, 2014)
Background: Tobacco is used in different forms among Indian women and the health effects can be seen irrespective of the way it is used. Objectives: To study the prevalence of tobacco use among the rural women in Mohanpur Block, West Tripura District and to study the factors associated with tobacco use. Materials and Method: This cross-sectional study was conducted in March, 2012, among 460 rural women in two randomly selected subcentre areas of Mohanpur Block. Results: The study revealed that 58.48% of the rural women were current consumer of tobacco, whereas the prevalence of ever tobacco users was 64.13%. Beetle leaf and nut with tobacco was the most common form of tobacco use with 57.40 % respondents using it. The most common reason cited for tobacco use was 'using it as a group habit' by 32.30 % respondents. Multiple logistic regression analysis showed that tobacco use was significantly low between 15-30 years of age (p value- 0.047), and was significantly high among those who were illiterate (p value- 0.014) or had primary education (p value- 0.013). Conclusion: The study showed a high prevalence of tobacco use by rural women which necessitates active intervention by formulating cessation and prevention programs.